A Randomized Controlled Trial of Concentrated ERP, Self-Help and Waiting List for Obsessive- Compulsive Disorder: The Bergen 4-Day Treatment - Launes, Gunvor; Hagen, Kristen; Sunde, Tor; Öst, Lars-Göran; Klovning, Ingrid; Laukvik, Inger-Lill; Himle, Joseph A.; Solem, Stian; Hystad, Sigurd W.; Hansen, Bjarne; Kvale, Gerd (Frontiers in Psychology, 2019)
Abstract Background: The Bergen 4-day treatment (B4DT) is a concentrated exposure-based treatment for patients with Obsessive-Compulsive Disorder (OCD) delivered during four consecutive days. The B4DT has in a number of open trials demonstrated promising results as approximately 90% of patients gain reliable clinical change post-treatment and nearly 70% are recovered on a long-term basis. Methods: The current study is the first randomized controlled trial evaluating the effects of the B4DT. Forty-eight patients diagnosed with OCD were randomized to B4DT, self-help (SH), or waiting list (WL) with 16 patients in each condition. All participants randomized to the B4DT underwent the treatment without any attrition. Results: The B4DT yielded significantly better effects than control conditions on measures of OCD, depression, and generalized anxiety. The response rate (≥ 35% reduction of the individual patient’s pre-treatment Y-BOCS score) was 93.8% in B4DT, 12.5% in SH and 0% in WL, while remission rate (response criterion is fulfilled and the post-treatment Y-BOCS score is ≤ 12 points) was 62.5%, 6.3%, and 0% respectively. Furthermore, patients who had received the B4DT, showed improved work- and social functioning. None of the patients treated with B4DT showed signs of deterioration. In comparison, one patient in the self-help condition was in remission, and one showed significant clinical improvement, whereas the remaining showed no change. Conclusion: The results add to the literature supporting the effectiveness of the B4DT for patients suffering from OCD.